THE IMPORTANCE AND PERFORMANCE ANALYSIS OF COMPENSATION PROGRAM BASTIANOS RESORT IN LEMBEH - Mandagi, Michelle Celine (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2016)
In this era of globalization, it is important to build a sustainable business as business is developing rapidly in Indonesia. Competition has increased tremendously in businesses. Therefore, human resource plays an essential role in determining the future of the business. In any business, it needs to build a good team of working professionals which is the responsibility of the human resource. This research is conducted in order to analyze how important is the compensation program and how is the performance of compensation program for employees using Importance Performance Analysis at Bastianos Resort in Lembeh. The sample of this research is the employees of Bastianos Resort in Lembeh as many as 43 employees. The result of this result reveals that insurance and salary are very important to the employees and the level of performance is also high. Since, the other indicators perceive to have low importance, this research suggest that Bastianos Resort in Lembeh should allocate the resources from unimportant indicators to salary and insurance to increase the employees’ motivation to work. Keywords: compensation, importance and performance analysis